Detection of Microorganisms in Low-Temperature Water Environments by in situ Generation of Biogenic Nanoparticles - Skladnev, Dmitry A.; Vasilyeva, Lina V.; Berestovskaya, Yulia Yu.; Kotsyurbenko, Oleg R.; Kalenov, Sergei V.; Sorokin, Vladimir V. (Frontiers in Astronomy and Space Sciences, 2020)
A new nanobiotechnological approach for detection extraterrestrial Earth-like biological forms is proposed. The approach is based on the ability of microbial cells to reduce artificially added cations with the generation of crystalline nanoparticles (NPs) from zero-valent atoms. The method is named DBNG (Detection of Biogenic Nanoparticles Generation). The subglacial low-temperature oligotrophic the Antarctic Lake Untersee was used as a model of putative extraterrestrial water environments inhabited by the Earth-like type microorganisms. The DBNG protocol for the comparative study of microbial communities of low-temperature oligotrophic environments was optimized on the base of experiments with the pure culture of psychoactive bacterium Cryobacterium sp. 1639 isolated earlier from the Lake Untersee. The formation of silver nanoparticles (AgоNPs) has been conducted in natural water samples of three horizons at low temperature (+5оC), which was in the temperature range registered in the Lake Untersee. The generation of biogenic AgоNPs was detected only at the presence of indigenous microorganisms in all studied samples. No AgоNPs generation was observed in the Lake water samples artificially free of cells or exposed to pasteurization (two types of controls). The miniature microfluidic chip for an automated version of the device based on using different analytical methods for recording in situ formed biogenic nanoparticles is proposed. The device allows detecting the biological objects directly at the sampling site.